(untitled) (Patan Prospective Journal, 2024)
The Woman Who Climbed Trees (2023) by Smriti Ravindra is a soul-stirring novel that showcases the miserable plight of women in a society governed by males. Marriage, gender discrimination, power relations between male and female, and toils of women in the family lead to their confinement within the frameworks staked out for them by men. Women suffer, are subjugated and subordinated, and are yet indispensible for running the family, where they are pulled by the traditional roles trusted upon her. But women’s access to education, employment, and socio political awareness has helped them achieve personhood. They no longer want to be connected to and defined by the societal and cultural norms of the patriarchal structure. The objective of this paper, therefore, is to examine and explore the theme of how women in the novel make resistance, claim space for themselves, and search for their identity. Through the lives of three women across different generations, Kaveri, Meena, and Priti, the novelist beautifully captures the complexities of love, acceptance, estrangement, and self-discovery, highlighting the evolution of self-assertion. The novel serves as a poignant exploration of human experience, anchored by protagonists, whose journeys serve as a microcosm of broader societal dynamics. Applying feminism as a research framework, this study delves into the protagonist’s journey of self-discovery and her challenges to patriarchal constraints. The analysis elucidates how the women in the novel navigate and resist a male-dominated social labyrinth.